2015
DOI: 10.4038/kjm.v4i1.7487
|View full text |Cite
|
Sign up to set email alerts
|

The External Auditor’s opinions and the stakeholders’ purposes: an empirical analysis in Sri Lanka

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…There are also some studies that were conducted by Chow and Rice, 1982;Dodd et al 1984;Tahinakis et al 2010;Moradi et al, 2011;Wickramasingha and Nanayakkara 2015 showing discussions regarding the relationship between audit opinion and stock return. While no impact was found between audit opinion and stock return in these studies above, in the studies conducted by Firth 1978, Dopuch et al, 1986Loudder et al 1992; Choi and Jetter, 1992 a significant impact was found (Chen et al 2000:434).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some studies that were conducted by Chow and Rice, 1982;Dodd et al 1984;Tahinakis et al 2010;Moradi et al, 2011;Wickramasingha and Nanayakkara 2015 showing discussions regarding the relationship between audit opinion and stock return. While no impact was found between audit opinion and stock return in these studies above, in the studies conducted by Firth 1978, Dopuch et al, 1986Loudder et al 1992; Choi and Jetter, 1992 a significant impact was found (Chen et al 2000:434).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Journal of Business Research-Turk 869 market (Bessel et al, 2003;Duréndez Gómez-Guillamón, 2003;Contreras et al, 2007;Chen et al, 2016;Kabajeh et al, 2012, Wickramasingha andNanayakkara, 2015).…”
Section: İşletme Araştırmaları Dergisimentioning
confidence: 99%
“…Genel piyasa özelliğinin bir sonucu olduğu belirtilen denetim görüşlerinin, yatırımcılar açısından faydalı bilgiler sağlamadığı kanaati vurgulanmıştır. Wickramasingha ve Nanayakkara (2015), yatırım sürecinde denetim görüşlerinin etkinliğini belirlemeye yönelik olarak gerçekleştirilen araştırmalarını Sri Lanka merkezli olarak gerçekleştirmişlerdir. Kolombiya Borsası imalat endeksi kapsamında yer alan 31 firma örnekleminde ve 2008-2013 inceleme dönemine sahip araştırmada ANOVA yöntemi kullanılmıştır.…”
Section: Uluslararası İktisadi Ve İdari İncelemeler Dergisiunclassified